Background thermal contributions in testing the Unruh effect - Costa, Sandro S. [UNESP]; Matsas, George E. A. [UNESP] (American Physical Society (APS), 1995)
We consider inertial and acclerated Unruh-DeWitt detectors moving in a background thermal bath and calculate their excitation rate. It is shown that for fast moving detectors such a thermal bath does not affect substantially the excitation probability. Our results are discussed in connection with a possible proposal of testing the Unruh effect in high energy particle accelerators. © 1995 The American Physical Society.